2016
DOI: 10.3389/fpubh.2016.00146
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Incidence and Mortality of Ovarian Cancer during 2003–2012 in Jiangsu Province, China

Abstract: PurposeThe objective of this study is to investigate and analyze the epidemiologic characteristics and time trends of ovarian cancer incidence and mortality in Jiangsu Province of China during 2003–2012.MethodData were collected from eligible cancer registries in Jiangsu Province. Crude rates, age-specific rates, truncated age-standardized rate, and proportions of ovarian cancer were calculated. The Segi’s World Population was used to calculate age-standardized rates for world (ASW). Poisson distribution was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…OC, a gynecologic malignancy, is the sixth most common type of cancer and a well-known silent killer in females over the world. 1 A large percentage of patients with OC are diagnosed at their advanced stages, due to the obscure symptoms of early-stage OC, as well as the lack of effective diagnostic methodologies. 18 Previous studies have shown that the development of OC is closely involved with genetic alternation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OC, a gynecologic malignancy, is the sixth most common type of cancer and a well-known silent killer in females over the world. 1 A large percentage of patients with OC are diagnosed at their advanced stages, due to the obscure symptoms of early-stage OC, as well as the lack of effective diagnostic methodologies. 18 Previous studies have shown that the development of OC is closely involved with genetic alternation.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer (OC) is one of the most dangerous gynecologic malignancy and the sixth most common cancer in females over the world. 1 Researchers have paid many efforts and promoted the development in diagnostics and cytotoxic therapies. However, the 5-year survival rate of patients with advanced-stage ovarian cancer is still as low as 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, historically less developed countries with recent economic growth and lifestyle changes have seen increases in incidence and mortality rates. In China, the increase is apparent only among rural women rather than those in more developed, urban regions 2,41 . …”
Section: Descriptive Epidemiologymentioning
confidence: 99%
“…Of all primary ovarian tumors, approximately 90% are epithelial ovarian cancer, which can be classified pathologically into different types, such as serous, mucinous, endometrioid, clear-cell and transitional-cell carcinomas [2]. In recent years, nearly 70% of patients have been diagnosed with ovarian cancer when they are in the middle or advanced stage due to the lack of effective screening strategies [3], resulting in a relatively low5-year survival rate [4]. Given the above, a thorough understanding of the mechanism of ovarian cancer would be beneficial for the early diagnosis and clinical treatment of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%